A Random Laser Based on Hybrid Fluorescent Dye and Diamond Nanoneedles. Issue 2 (29th October 2018) - Duong, Ngoc My Hanh; Regan, Blake; Toth, Milos; Aharonovich, Igor; Dawes, Judith
Abstract : Random lasers use radiative gain and multiple scatterers in disordered media to generate light amplification. In this study, a random laser based on diamond nanoneedles that act as scatterers in combination with fluorescent dye molecules that serve as a gain medium has been demonstrated. Random lasers realized using diamond possess high spectral radiance with angle‐free emission and thresholds of 0.16 mJ. The emission dependence on the pillar diameter and density is investigated, and optimum lasing conditions are measured for pillars with spacing and density of ≈336 ± 40 nm and ≈2.9 × 10 10  cm −2 . Our results expand the application space of diamond as a material platform for practical, compact photonic devices, and sensing applications. Abstract : In this study, a random laser is realized for the first time by integrating Rhodamine 6G dye into a diamond nanoneedles matrix. This work paves the way to potential applications of diamond nanoneedles in imaging, sensing, and display technologies.